Protective vaccinations – legal and financial analysis - Dominika Trzeszczoń (Prawo Budżetowe Państwa i Samorządu)
The financial and legal aspects of preventive vaccinations in Poland form a subject of a research and analysis taken in this study. Due to the complex scope of considerations, it was also necessary to take into account issues that will allow to assess in a comprehensive manner a problem indicated in a title of this study. Thus, the research is made both from the legal and financial perspective, paying attention to the regulations contained in the budget act. This issue has not been thoroughly investigated by the doctrine, what makes this theme be a source of interesting analysis and conclusions. In this study, in the first place, general issues related to the constitutional regulations on preventive vaccinations are presented, with reference also to other legal acts regulating this issue. Subsequently, selected problematic issues, such as, for example, the analysis of the National Immunization Program, and also the Protective Vaccination Compensation Fund are analysed. The importance of preventive vaccinations and the issues related to their financing under the provisions of the Budget Act of 2022 and the Act of 5 December 2008 on preventing and combating infections and infectious diseases in humans were also analysed. The research covers also an expenditure on health care under the Act of 27 August 2004 on health care services financed from public funds.